2003
DOI: 10.1038/sj.bjc.6601041
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Fhit and p53 in Taiwanese surgically treated non-small-cell lung cancers

Abstract: Abnormalities of fragile histidine triad (FHIT) and TP53 have been found frequently in nonsmall cell lung cancers. In the current study, 263 primary nonsmall cell lung cancers were investigated for the expressions of Fhit and p53 by immunohistochemistry. Marked reduction of Fhit immunoreactivity (o10% positivity) in 156 (59%) tumours and overexpression of p53 protein (410% positivity) in 89 (34%) tumours were found. Reduced Fhit expression was also noted in most squamous cell carcinomas (80 out of 99, 81%), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
2
7
0
Order By: Relevance
“…Abnormalities of p53 expression by immunostaining were frequently found in lung cancer including 40 -70% of SCLCs and 40 -60% of NSCLCs. Previous reports, in our study of Taiwanese NSCLCs, have also indicated that p53 nuclear expression by immunostaining analysis detected more frequent stainable expression in squamous cell carcinoma than that in adenocarcinoma (Chang et al, 2003) In addition, p53 overexpression and the loss of Fhit expression has been significantly more common in tumours from smokers than those of nonsmokers (Chang et al, 2003).…”
supporting
confidence: 67%
See 1 more Smart Citation
“…Abnormalities of p53 expression by immunostaining were frequently found in lung cancer including 40 -70% of SCLCs and 40 -60% of NSCLCs. Previous reports, in our study of Taiwanese NSCLCs, have also indicated that p53 nuclear expression by immunostaining analysis detected more frequent stainable expression in squamous cell carcinoma than that in adenocarcinoma (Chang et al, 2003) In addition, p53 overexpression and the loss of Fhit expression has been significantly more common in tumours from smokers than those of nonsmokers (Chang et al, 2003).…”
supporting
confidence: 67%
“…It was previously indicated that the genetic changes at the FHIT locus may be correlated with p53 mutations (Burke et al, 1998;Marchetti et al, 1998;Chang et al, 2003), while other investigators found no statistically significant correlation between FHIT and p53 abnormalities in NSCLCs (Nelson et al, 1998;Geradts et al, 2000). By examining the FHIT/ p53 profiles, we noticed that the nine cases with synergistic effect of LOH at FHIT locus and p53 overexpression included six squamous cell carcinomas and three adenocarcinomas.…”
Section: Discussionmentioning
confidence: 60%
“…Some studies have shown that p53 mutation or overexpression is an indicator of poor prognosis, especially in patients with lung adenocarcinoma [12]. Our previous studies revealed that p53 expression was an independent prognostic factor in stage I NSCLC [18] and was associated with distant metastasis in NSCLC patients and poorer survival in adenocarcinoma patients [23]. The present study showed that p53 mutation was associated with tumor relapse in stage I, but not stage IA, patients with surgically resected small adenocarcinomas, which suggested that p53 mutation was a risk factor…”
Section: Journal Of Surgical Oncologymentioning
confidence: 99%
“…Several studies, using either immunohistochemical or molecular methods, showed a significant loss of Fhit in lung cancers from smokers compared with lung cancers from nonsmokers (3)(4)(5)(6)(7)(8)(9). Interestingly, a dose-dependent decrease of Fhit methylation was observed in bronchoalveolar lavage cells from cancer-free patients undergoing fiber optic bronchoscopy, as related to the number of cigarettes smoked in a lifetime (10).…”
Section: Introductionmentioning
confidence: 98%